Regioselective synthesis of C3 alkylated and arylated benzothiophenes - Harry J. Shrives (Nature Portfolio, 2017)
Benzothiophenes are common motifs in bioactive compounds, but selective functionalization at C3 is challenging. Here the authors report a method starting from benzothiophene S-oxides via an interrupted Pummerer reaction, giving access to a range of C3-alkylated and -arylated products.